Cantilever enhanced photoacoustic spectroscopy: The First two decades - Koskinen, Vesa (fi=Turun yliopisto|en=University of Turku|, 2024)
Two decades ago, the first experiments with a novel optical microphone using a small silicon cantilever as its sensing element were conducted at the University of Turku. In retrospect, those experiments revealed the potential enhancing the sensitivity of photoacoustic spectroscopy (PAS) by using this cantilever microphone as a replacement for the conventionally used condenser microphone. In just a few years, this replacement had led to a very sensitive technique, nowadays known as cantilever enhanced photoacoustic spectroscopy, CEPAS. The introduction of CEPAS and its first years of development including a complete physical model of the system are described in the first part of this thesis. Covering the first two decades after the introduction of CEPAS, the latter part presents a unique retrospective study on its influence on the applied spectroscopy research. During the introduction of CEPAS as well as in the early development of the technique, a broadband IR source was used. For the comparison to the other techniques, the same unoptimized prototype with a tunable diode laser source was used to detect carbon dioxide. The achieved normalized noise equivalent sensitivity (NNEA) was at the same level as the best ever reported by PAS until then. The detector was then optimized for laser sources mainly by changing the properties of the cantilever and the design of the cell, that enabled minimizing the dead volume of the sample cell. This optimization of the detector in 2007 led to a NNEA value of 1.7 × 10−10cm−1W/√Hz. At that time it was the best ever reported in PAS and is still – after fifteen years – among the very best ones. The realized sensitivity as well as the presented future improvements were based on the accuracy of the developed physical model. CEPAS has been used in several applications, ranging from medical and pharmaceutical sciences to the detection of radioactive and toxic materials or greenhouse gases. In several application areas it is only just taking its first steps. CEPAS has also inspired hundreds of scientific publications, numerous research projects as well as new techniques. Nowadays, it has become a recognized and functional technique that has already had and still has impact on several scientific fields worldwide.